2015
DOI: 10.1007/s10563-015-9187-1
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of One-Dimensional Metal Nanostructures for Electrocatalysis

Abstract: Nanostructures of metals are of great importance in the area of catalysis due to their distinct physicochemical properties compared to their bulk counterparts. Size and morphology dependent properties of metal nanostructures provide a rational approach toward designing a highly efficient catalytic materials. In particular, onedimensional (1D) metallic nanostructures in the shapes of wires, rods and tubes have recently been studied with great interest due to their potential uses as electrocatalysts for oxidatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 162 publications
0
17
0
Order By: Relevance
“…To estimate the overall oxygen‐electrode activity, we quantitatively compared the overpotential of the tested catalysts in terms of the potential difference (Δ E=E OER − E ORR ) if the ORR current density reaches −2 mA cm −2 and the OER current density reaches 10 mA cm −2 , as shown in Table S3. The RuO 2 /Co 3 O 4 NWs exhibited a substantially improved oxygen activity value of 0.91 V with respect to these values for the Co 3 O 4 NWs of 1.05 V and for the KB of 1.27 V. The improved catalytic activity of the RuO 2 /Co 3 O 4 NWs might come from (i) lowering overpotential for reactions with oxygen by highly active RuO 2 nanoparticles as co‐catalyst, (ii) facile pathway for electron and mass transfer with the 1 D anisotropic morphology, and (iii) enhanced electrical conductivity by the conductive RuO 2 in the composite system as confirmed by electrochemical impedance spectroscopy (EIS, see Figure S6). Chronoamperometry tests showed that RuO 2 /Co 3 O 4 NWs have superior stability compared to commercial Pt/C during the ORR and OER processes (for more details, see Figure S7).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To estimate the overall oxygen‐electrode activity, we quantitatively compared the overpotential of the tested catalysts in terms of the potential difference (Δ E=E OER − E ORR ) if the ORR current density reaches −2 mA cm −2 and the OER current density reaches 10 mA cm −2 , as shown in Table S3. The RuO 2 /Co 3 O 4 NWs exhibited a substantially improved oxygen activity value of 0.91 V with respect to these values for the Co 3 O 4 NWs of 1.05 V and for the KB of 1.27 V. The improved catalytic activity of the RuO 2 /Co 3 O 4 NWs might come from (i) lowering overpotential for reactions with oxygen by highly active RuO 2 nanoparticles as co‐catalyst, (ii) facile pathway for electron and mass transfer with the 1 D anisotropic morphology, and (iii) enhanced electrical conductivity by the conductive RuO 2 in the composite system as confirmed by electrochemical impedance spectroscopy (EIS, see Figure S6). Chronoamperometry tests showed that RuO 2 /Co 3 O 4 NWs have superior stability compared to commercial Pt/C during the ORR and OER processes (for more details, see Figure S7).…”
Section: Resultsmentioning
confidence: 99%
“…The morphology of the nanostructure of catalysts can directly affect their electrochemical performance. Thanks to their anisotropic electron‐transport properties and large surface‐to‐volume ratio, one‐dimensional (1 D) nanostructure materials, such as nanorods, nanowires, and nanotubes, have been widely studied in various electrochemical energy systems of fuel cells, solar cells, and batteries . Among the synthetic methods used to produce 1 D nanostructures, electrospinning has received much attention owing to its simple process; low fabrication cost; and easy control of the morphology, composition, and surface topologies of electrospun nanowires …”
Section: Introductionmentioning
confidence: 99%
“…These materials have been utilized in the field of electrocatalysis and energy conversion. [65][66][67] As for electrocatalysts of the ORR, 1D MÀ NÀ C materials have also attracted great attention. [68] The morphologies of reported 1D MÀ NÀ C materials include nanofibers, nanowires, nanorods, and nanotubes.…”
Section: D Metal-nitrogen-carbon Materials For the Oxygen Reduction mentioning
confidence: 99%
“…

3Ag 0 Au III 3Ag I Au 0 ( ) ( ) ( ) ( )

With the advent of nanosciences, this simple reaction has undergone considerable interest, because both partners of Reaction (1) are stabilized as nanoparticles by a great variety of organic or inorganic ligands or macromolecules. [8][9][10] Numerous methods have been developed for the design and synthesis of BNPs and BNCs and have been reviewed, [11][12][13][14][15][16][17][18][19][20][21] and among them, the galvanic reduction (GR) stands as one of most commonly employed methods. How the interest in mixing metals applies to the nanoworld has attracted considerable attention from researchers.

…”
mentioning
confidence: 99%
“…[3][4][5][6][7] For instance BNPs catalysts most often show unprecedented chemical conversion, surpassing the performances of MNPs, because of their specific functionality involved in the overall reaction mechanism. [8][9][10] Numerous methods have been developed for the design and synthesis of BNPs and BNCs and have been reviewed, [11][12][13][14][15][16][17][18][19][20][21] and among them, the galvanic reduction (GR) stands as one of most commonly employed methods. Moreover, very recent findings forming the new outstanding area of the anti-galvanic reduction (AGR) deserve specific consideration.…”
mentioning
confidence: 99%